Gestión de talento humano y el desempeño laboral en la empresa Agricommerce Cía. Ltda. De la ciudad de Riobamba. - Tierra Iza, Liliana Lisbeth (2023)
The following work entitled "Human Talent Management and Job Performance at Agri commerce Ltd. Co. in the City of Riobamba," has as main objective to propose a human talent management model to improve the achievement at the mentioned company, which will have a positive impact on its employees' performance. The hypothetical deductive method was applied, and the study population included all 7 company employees. The necessary information was collected using a survey questionnaire and processed with Excel. To test the hypothesis, a chi-squared value of 14 was used, which was greater than the tabulated value of 7.81, leading to the rejection of the null hypothesis and the acceptance of the alternative hypothesis that "human talent management affects the job performance of Agri commerce Ltd. Co." A proposal was then created, specifying each category with a manual. Finally, the conclusions and recommendations were presented, serving as a guide for the company's executives.